Planning Considerations for Tourism in the Minho-Lima Region (Northwest Portugal) - Remoaldo, Paula (2013)
In administering their territories, most local municipalities aim to preserve their natural, historical and ethnographical resources while simultaneously using them to increase revenue and employment. In order to efficiently promote the products and services available and attract tourists, decision makers, private and public, need to know and incorporate tourists’ preferences in their marketing strategies. In this chapter we illustrate the use of stated preferences as an instrument to identify national and foreign tourists’ preferences regarding the products and services that the touristic destination of the Minho-Lima region (Northwest Portugal) should offer. As a starting point, we have taken the three general groups of touristic resources mentioned above as attributes. We take Ponte de Lima, a municipality in this region that has a strong cultural tourism potential as an example to identify possible future tourism scenarios for this territory. We believe the previously identified methodology can be a valuable instrument in the identification of the strengths and weaknesses of the selected territory and, thus, support the decision making process behind its future tourist development and marketing strategies.